Ultrasonic pretreatment of soft wood biomass prior to conventional pyrolysis: Scale-up effects and limitations. (May 2019) - Cherpozat, Lucie; Loranger, Eric; Daneault, Claude
Abstract: After finding a successful ultrasonic wood treatment that enhanced bio-oil yield prior to pyrolysis in our laboratory, the next logical step was the scaling up of the process. Hence, this work aims to study the effects and limitations of an ultrasonic wood pretreatment scale-up from the laboratory scale (200 g) to the pilot scale (700 g). Wood chips were characterized by elemental chemical analysis, X-ray Photoelectrons Spectroscopy (XPS), Thermogravimetric Analysis (TGA), and Scanning Electron Microscopy (SEM). XPS and TGA did not show any change in the surface chemical composition. However, the SEM images clearly showed that the treatment in the bath allowed surface cleaning of the wood, thus creating an opening in the wood physical structure and allowing better heat transfer, as seen in the TGA analysis. As often found in such an endeavor, it was shown that these same ultrasonic conditions applied to a larger scale did not lead to the same results. The wood from the pilot scale unit (PSU) exhibited the same characteristics as the untreated wood. Thus, PSU did not allow an opening in the wood structure, as shown in the SEM images, which would have resulted in better heat transfer and thus in a higher bio-oil yield. From our experience with such systems, a hypothesis could be dependent on the greater efficiency of the PSU, especially at high frequencies, which could lead to the opposite effect than what was expected. Further investigations are necessary to overcome this limitation and to truly assess the phenomenon. Highlights: No wood chemical modifications have been induced by the pilot scale ultrasonic treatment. Wood physical modifications are found and are different when changing scales (bath to pilot). Pilot scale unit powerfulness is the limiting factor for the treatment effectiveness.